2009
DOI: 10.1016/j.intcom.2009.06.001
|View full text |Cite
|
Sign up to set email alerts
|

UbiCicero: A location-aware, multi-device museum guide

Abstract: Interactive games in museums User interface software and technology a b s t r a c tIn this paper, we propose UbiCicero, a multi-device, location-aware museum guide able to opportunistically exploit large screens when users are nearby. Various types of games are included in addition to the museum and artwork descriptions. The mobile guide is equipped with an RFID reader, which detects nearby tagged artworks. By taking into account context-dependent information, including the current user position and behaviour … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
39
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 88 publications
(46 citation statements)
references
References 15 publications
(13 reference statements)
0
39
0
1
Order By: Relevance
“…For example, modern museums and art galleries often provide visitors with location-aware personal audio devices, or more recently smartphone applications [1,16,23], to augment their visiting experiences and provide details on an exhibit-by-exhibit basis as visitors move through a collection. Such use of technology to augment and enhance the visiting experience not only improves a visitor's experience by making the materials more accessible and enjoyable, but can also benefit institutions like museums through the development of brand and loyalty [25].…”
Section: Supporting Scientific Outreachmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, modern museums and art galleries often provide visitors with location-aware personal audio devices, or more recently smartphone applications [1,16,23], to augment their visiting experiences and provide details on an exhibit-by-exhibit basis as visitors move through a collection. Such use of technology to augment and enhance the visiting experience not only improves a visitor's experience by making the materials more accessible and enjoyable, but can also benefit institutions like museums through the development of brand and loyalty [25].…”
Section: Supporting Scientific Outreachmentioning
confidence: 99%
“…For example, large interactive displays have been leveraged to provide interactive exhibit content for museum visitors [18,20]. Similarly, emerging trends in mobile devices and augmented reality have been explored as a means of making physical spaces more supportive of outreach activities [1,16,23]. In this work, we explore using two technologies in these domains: large interactive displays, and location-aware mobile devices.…”
Section: Interactive Surfaces and Spacesmentioning
confidence: 99%
“…Passive context-aware: the application presents the changed context, sensor data, to the user and lets him/her take control of decisions about how the application behaves. Much research has shown the significance of context-awareness in education (Yau and Joy, 2009;Fisher et al, 2009;Ghiani et al, 2009;Bhaskar and Govindarajulu, 2010;Chiou et al, 2010). Fisher et al (2009) argue that the use of mobile devices such as tablet PCs in education can enhance the teaching experience of lecturers, as well as the quality of the learning experience of students.…”
Section: Context-aware and Location-based Mobile Learningmentioning
confidence: 99%
“…Courses with assignments that include student presentations and group projects can motivate students to submit their assignment on a Tablet PC or smartphone device. Jeng et al (2010) indicated mobile technology can construct innovative learning experiences. Granting students the ability to submit assignments on a mobile technology device may not only improve students' efficacy and selfdirectedness with mobile technology and produce much more robust results, but also provide the instructor more time in class to expand teaching opportunities by saving time allotted for student and group presentations in class.…”
Section: Recommendationsmentioning
confidence: 99%
“…The increasing of use of mobile technologies to deliver educational content is changing the landscape of our educational system. Mobile technology has the ability facilitate learners' learning process and create new and innovative learning opportunities (Jeng, Wu, Huang, Tan, & Yang, 2010). Lowenthal (2010) suggested mobile technology offers universities benefits such as increasing enrollment and broadening the student population both demographically and geographically.…”
mentioning
confidence: 99%